Dietary glycemic load, insulin load, and weight loss in obese, insulin resistant adolescents: RESIST study. Issue 1 (February 2015) - Joslowski, Gesa; Halim, Jocelyn; Goletzke, Janina; Gow, Megan; Ho, Mandy; Louie, Jimmy C.-Y.; Buyken, Anette E.; Cowell, Chris T.; Garnett, Sarah P.
Summary Background & aims The optimal dietary approach for weight loss and improving insulin sensitivity in adolescents is unknown. This study aimed to explore the association between the estimated insulin demand of the diet, as measured by glycemic and insulin load, weight loss, percentage body fat and insulin sensitivity index (ISI) in obese adolescents with clinical features of insulin resistance and/or prediabetes after a 3 month lifestyle and metformin intervention. Methods Secondary data analysis of 91 adolescents (median age 12.7 years (range 10.1–17.4) participating in a randomized controlled trial, known as RESIST; ACTRN12608000416392. Weight change between baseline and 3 months was measured by BMI expressed as percentage of the 95th centile (BMI %95). Body composition was measured by dual energy X-ray absorptiometry and ISI was determined by an oral glucose tolerance test. Results Higher dietary glycemic load and insulin load were associated with less weight loss (BMI %95), adjusted for sex and pubertal stage, β = 0.0466, P = 0.007 and β = 0.0124, P = 0.040, respectively. Inclusion of total energy intake in the model explained observed associations between dietary glycemic load and insulin load and change in BMI %95. Neither dietary glycemic load nor insulin load were associated with changes in percentage body fat or ISI. Dietary glycemic index and macronutrient content (% of total energy) were not associated to changes in BMI %95, percentage body fat or ISI. Conclusion Reduced energy diet contributes to weight loss in obese, insulin resistant adolescents. Diets with a lower insulin demand were associated with a lower energy intake and may hence assist with weight loss.